Microfluidics based electroporation for inactivation of microorganisms - Pudasaini, Sanam (Nanyang Technological University, 2020)
Disinfection of water has prevented humans from deadly water-borne diseases for many years. Current methods of bacterial inactivation include the use of ultraviolet radiation (UV), chlorine compounds, ozonation, etc., which pose issues such as high energy consumption, the formation of disinfection by-products, pathogen regrowth, etc. This PhD thesis reports electroporation-based inactivation devices that achieve highly efficient bacterial inactivation at significantly lower voltage compared to the conventional bulk electroporation device. The method involves the use of insulating structures such as micropillars and microbeads that create multiple electroporation zones with enhanced local electric field strengths enabling bacterial electroporation at low voltages. Firstly, as a proof of concept, a simple microfluidic electroporation device that includes an array of micropillars was developed. Nearly 63% of inactivation of Saccharomyces cerevisiae was achieved at a flowrate of 2.5 mL/h, which was higher than the 24% cell inactivation observed for a micropillar-free reference device subjected to the same conditions. Further, to investigate the effect of micropillar shapes on the inactivation performance, two microfluidic devices with different base geometries (circular and rhombus) were developed. The effect of DC and AC voltages were also examined along with other parameters, including applied frequency, and flowrate. The parametric experimental studies showed a higher log removal efficiency for the rhombus-shaped micropillar device than the circular micropillar device, where Escherichia coli and Enterococcus faecalis were used as two model bacteria. Scanning electron microscopy (SEM) imaging was performed confirming the membrane damage was caused by electroporation. Secondly, an electroporation-based bacterial inactivation device operating in an insulating microbeads-enhanced electric field was developed. Electric voltage was applied to a pair of mesh electrodes inside the chamber consisting of densely packed microbeads. The microbeads generate locally high electric field strengths at low applied voltages, which were sufficient for the electroporation of bacteria. The effect of microbeads on the inactivation performance was assessed by comparing the performance of the microbead device with that of a microbead-free device under the same operating conditions. The results showed that the microbead-free device achieved only 0.57 log removal—eightfold lower than that for the device with microbeads. The energy consumption of the device was much lower than that of the UV inactivation of bacteria. Finally, a contactless insulator-based dielectrophoresis device was developed to enable bacterial trapping in the region of high electric field strength using positive DEP and thereby increasing the holding time of bacteria for a better electroporation performance. The device involved two side channels that were filled with liquid metal and were isolated from the main channel by a thin strip of polydimethylsiloxane (PDMS). The developed finite element electric field simulation showed good agreement with theoretical electrical circuit modeling in determining the voltage-drop across the medium. Significantly higher bacterial trapping and inactivation were achieved at significantly lower voltages compared to the conventional bulk electroporation devices. Overall, the reported method in this PhD work could potentially be used in different applications of electroporation such as water treatment, food processing and continuous extraction of intracellular components.